The roles of educators in the inclusive process from the active-learning point of view - Petrović, Ivana P. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2019)
The process of educational reform of an inclusive type a large part of the world has been included in, aims to improve the quality of education as a whole. Planned changes not only concern developmentally impaired children, but they also concern the education of all children, encompassing all marginalized groups and striving to make changes that lead to better education and more inclusive society. Similarly, the Active Learning project is a serious attempt to innovate and modernize our education, which aims at changing the learning/teaching methods and the position of the child/student in the kindergarten/school, in order to improve the quality of education and create an inclusive environment for all children. Since the educator is the first person whom the child meets and spends the most time with in kindergarten and since the process of inclusion in kindergartens largely depends on the teachers, it is necessary to provide them with the most optimal conditions for work and quality training in order to recognize developmental disorders in children pre-school age and adjust the way of work to their individual differences. For this reason, in this paper we will try to show the roles that the educator has or should have in an inclusive process in accordance with the basic specifics and principles of active learning. This is important because the way in which educators understand their roles and responsibilities influences their way of working with children, the level of engagement of children in common learning activities, as well as what and to what extent the children will learn.